Discovering the self-concept of a selected sample of Filipino school-aged children - Dy, M. R. (2003)
This study explored the various dimensions and self-presentations of the self-concept in school-aged children (7-11). It also looked into how children define their self concepts in terms of positivity-negativity and consistency/stability. The findings of the study were in the following a) the dimensions which were highly reflected in the respondents statements were the personality, physical, and cognitive dimensions b) the " ideal" selves were based mainly on their dream professions, being good and intelligent; the "could" selves were related to their dream alternate professions, being good and intelligent; and the "afraid-to-be" selves were not to become bad people, be in occupations the don't want to be and be dull/slow; c) that positive and negative trait were generally reported as remaining consistent in the self-concept and d) that positive and negative traits were generally reported as remaining consistent in the self-concept and d) that the respondents, generally look at themselves positive. Further studies on wider group children can enrich the understand of the dynamics of the self-concept formation and the development as influenced by significant social environments like the family and the school in the Philippine setting.